"Optimized" delivery of intracoronary supersaturated oxygen in acute anterior myocardial infarction: A feasibility and safety study. Issue 1 (2nd April 2015) - Hanson, Ivan D.; David, Shukri W.; Dixon, Simon R.; Metzger, D. Christopher; Généreux, Philippe; Maehara, Akiko; Xu, Ke; Stone, Gregg W.
Abstract : Objectives: We sought to evaluate the feasibility and safety of catheter‐based supersaturated oxygen (SSO2 ) delivery via the left main coronary artery (LMCA) following primary percutaneous coronary intervention (PCI). Background : In the multicenter, randomized AMIHOT‐II trial, SSO2 delivered into the proximal or mid left anterior descending (LAD) artery via an indwelling intracoronary infusion catheter in patients with acute anterior ST‐segment elevation myocardial infarction (STEMI) following primary PCI significantly reduced infarct size but resulted in a numerically higher incidence of safety events. Methods : Patients with acute anterior STEMI presenting within 6 hr of symptom onset were enrolled at three centers. Following successful LAD stenting, SSO2 was infused into the LMCA via a diagnostic catheter for 60 min. The primary safety endpoint was the 30‐day rate of target vessel failure (composite of death, reinfarction, or target vessel revascularization). Cardiac magnetic resonance imaging (cMRI) was performed at 3–5 and 30 days to assess infarct size. Results : Twenty patients with acute anterior STEMI were enrolled. The infarct lesion was located in the proximal LAD in 7 cases (35%) and the mid LAD in 13 cases (65%). Following primary PCI, SSO2 was delivered successfully in all cases. Target vessel failure within 30 days occurred in 1 patient (5%). Median [interquartile range] infarct size was 13.7% [5.4–20.6%] at 3–5 days and 9.6% [2.1–14.5%] at 30 days. Conclusions : Following primary PCI in acute anterior STEMI, infusion of SSO2 via the LMCA is feasible, and is associated with a favorable early safety and efficacy profile. © 2015 Wiley Periodicals, Inc.